2002
DOI: 10.1046/j.1525-1438.2002.01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of morphometric, DNA cytometric features, and other prognostic markers on survival of endometrial cancer patients in northern Norway

Abstract: The objective of this study was to evaluate the prognostic value of nuclear morphometric features and DNA ploidy by flow cytometry next to depth of myometrial invasion and vascular invasion in endometrial cancer of all FIGO stages. A total of 123 women (103 FIGO stage I, eight stage II, and 12 stage III and IV) from northern Norway were studied. The follow-up period was between 7 and 19 years. The median age of patients was 62 years. The primary surgery was performed in the University Hospital of Tromso or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…However, multivariate analyses were carried out in a limited number of cases and events [33], using dichotomized DNA ploidy with dissimilar criteria for classification [3, 9, 17], and incorporating usually aneuploid type 2 carcinoma [3, 11]. Therefore, it is difficult to draw a conclusion on the prognostic superiority DNA ploidy over the traditional prognostic markers in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, multivariate analyses were carried out in a limited number of cases and events [33], using dichotomized DNA ploidy with dissimilar criteria for classification [3, 9, 17], and incorporating usually aneuploid type 2 carcinoma [3, 11]. Therefore, it is difficult to draw a conclusion on the prognostic superiority DNA ploidy over the traditional prognostic markers in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the DNA ploidy studies, all the histological subtypes are included in the analyses making the interpretation of DNA ploidy findings in a definite subtype difficult [3, 16, 17]. Furthermore, DNA ploidy statuses and the DNA index (DI) of aneuploid tumor are associated with the histological subtypes [18].…”
Section: Introductionmentioning
confidence: 99%
“…In endometrial carcinoma it has been repeatedly shown that patients with diploid tumours have a better prognosis than do those with aneuploid tumours, and that on multivariate analysis aneuploidy and the mitotic index are independent prognostic indicators, 82–109 with aneuploidy being significantly related to an increased risk of nodal metastases, recurrence and disease‐related death. There have been only a few dissenting voices from this consensus, 110–114 but these have been sufficiently emphatic to indicate that the last word on this topic may not yet have been spoken. In most studies ploidy has been a stronger prognostic factor than any other tumour‐associated variable with the possible exception of positive immunostaining for p53 115 .…”
Section: Endometrial Adenocarcinomamentioning
confidence: 99%
“…Four of the studies demonstrated independent prognostic impact of DNA ploidy also in multivariate models, hazard ratios (HR) in the range 2.6-6.5 (10,26,30,31), and one study borderline significant impact, P 5 0.10 (27). Two of the studies did not demonstrate any independent association between DNA ploidy and prognosis in multivariate analysis (28,29), and in one study this analysis was not performed (25). The included studies differ, and some even lack adequate description of methodology, inclusion criteria and other clinical and histopathological characteristics explored (25), making comparisons difficult with more recent studies applying present "state of the art" for histopathologic subtyping and surgical staging (10).…”
Section: Dna Ploidy As a Prognostic Marker In Endometrial Carcinoma Ementioning
confidence: 96%
“…Eight studies evaluating the effect of DNA ploidy in primary tumors retrieved from hysterectomy specimen on prognosis in endometrial cancer FIGO stages I-IV were identified (10,(25)(26)(27)(28)(29)(30)(31). Characteristics and results of the different studies are presented in Table 2.…”
Section: Dna Ploidy As a Prognostic Marker In Endometrial Carcinoma Ementioning
confidence: 99%